Organoleptic product study of Gyoza products with natural dyes extracted from purple sweet potatoes. Issue 1 (October 2021) - Natanael,; Wijaya, Hengki; Dirpan, A
Abstract: The use of purple sweet potato as a natural colour extract in food processing is one of the food industry's efforts to draw customer attention, and its use is deemed healthier for eating, as shown in processed food Gyoza. Wheat flour, cornstarch, tapioca flour, and purple sweet potatoes that have been boiled to retain the atocyanin chemicals and as natural colours are the main ingredients in manufacturing Gyoza skin (dumpling). Organoleptic tests on aroma, taste, texture, and color were employed as the research approach. The findings revealed that 22 respondents thought the Purple Gyoza product was satisfactory and quite appealing for customer consumption when considering the taste and correct processing procedure.